2007
DOI: 10.1525/maq.2007.21.3.324
|View full text |Cite
|
Sign up to set email alerts
|

The Meaning of the Present: Hope and Foreclosure in Narrations about People with Severe Brain Damage

Abstract: In this article, I consider narratives told within a clinical setting. I argue that personnel in a day center for people with acquired brain damage are constantly involved in narrating about the disabled participants. The negotiation of who the participant is, and foremost will be, is in constant negotiation in regard to issues of hope. I further argue that hope is a meaning-making process and, as such, it has been defined as crucially connected to time. Hope has been said to enable a connection between the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(43 citation statements)
references
References 23 publications
0
43
0
Order By: Relevance
“…The example indicates the challenge of incorporating the minimal self into the narrative self, providing meaningful self-narratives to rebuild/reorganise identity. The ''new'' body must be incorporated into their life history/self-narrative (Antelius, 2007), implying that meaningful activities and interaction must take place. We consider meaningful activities closely related to being in control of one's own actions or having a sense of agency.…”
Section: Self-narratives and Identitymentioning
confidence: 99%
“…The example indicates the challenge of incorporating the minimal self into the narrative self, providing meaningful self-narratives to rebuild/reorganise identity. The ''new'' body must be incorporated into their life history/self-narrative (Antelius, 2007), implying that meaningful activities and interaction must take place. We consider meaningful activities closely related to being in control of one's own actions or having a sense of agency.…”
Section: Self-narratives and Identitymentioning
confidence: 99%
“…Of the 12 studies included in this review, two were qualitative studies (Antelius, 2007; Howes, Benton, & Edwards, 2005); two were mixed methods studies (only qualitative findings reported; Alston, Jones, & Curtin, 2012; Chamberlain, 2006); and the remaining eight were quantitative studies (Bay et al, 2009; Chase et al, 2012; Colantonio, Mar, et al, 2010; Hart et al, 2011; Peleg, Barak, Harel, Rochberg, & Hoofien, 2009; Strom & Kosciulek, 2007; Van der Horn, Spikman, Jacobs, & van der Naalt, 2013; Wilbur & Parente, 2008); The qualitative studies used various methods, including open coding (Alston et al, 2012); content analysis (Chamberlain, 2006); and interpretive phenomenology (Howes et al, 2005). The majority of quantitative studies used self-reported questionnaires.…”
Section: Resultsmentioning
confidence: 99%
“…There was a large amount of variability in data collection time points, including multiple time points that were unspecified, 6 months or more postinjury (Howes et al, 2005; van der Horn et al, 2013), and 12 or more months postinjury (Hart et al, 2011). Finally, studies were conducted in various countries around the world, including five in the United States (Bay et al, 2009; Chase et al, 2012; Hart et al, 2011; Strom & Kosciulek, 2007; Wilbur & Parente, 2008); two in Australia (Alston et al, 2012; Chamberlain, 2006); one in Canada (Colantonio, Mar, et al, 2010); one in Wales (Howes et al, 2005); one in the Netherlands (van der Horn et al, 2013); one in Sweden (Antelius, 2007); and one in Israel (Peleg et al, 2009). …”
Section: Resultsmentioning
confidence: 99%
“…Severe disability has various connotations (Olney, 2001: 87); here it refers to both physical and verbal disabilities caused by brain damage in adult life that have had a profound impact on the participants' lives. Ways of communicating or interacting in so-called 'typical ways' have been altered and the participant no health: 13 (3) longer lives or works independently, being in constant need of around-theclock personal assistance or living in sheltered housing (Antelius, 2007).…”
Section: The Settingmentioning
confidence: 99%